Human detection implementation on UAVs in search and rescue operation / Muhammad Shahir Hakimy Salem, Fadhlan Hafizhelmi Kamaru Zaman and Nooritawati Md Tahir - Hakimy Salem, Muhammad Shahir; Kamaru Zaman, Fadhlan Hafizhelmi; Md Tahir, Nooritawati (Universiti Teknologi MARA, 2021)
Through the years, natural disasters keep happening and becoming more frequent and severe. Disasters can cause loss of property as well as human life. In disasters that cause mass fatalities, search and rescue operations are indeed vital and need to be conducted urgently. Unmanned aerial vehicles (UAV) or drones are the new emerging technology that has the capability to be deployed regularly to aid in search and rescue. By using UAV technology, it can speed up the search and rescue process and speed-up victims’ identification process before the body decomposes. Compared to conventional search and rescue operations, UAVs are more appropriate and economical due to their small-scale size of equipment. This paper presents reviews on the use of human detection based on UAV and technology in the scope of search and rescue operations for natural disasters.